ANALISIS PERBANDINGAN RISIKO KONTRAK LUMPSUM DAN KONTRAK UNIT PRICE PADA PROYEK KONSTRUKSI DI KOTA MANADO - Mandagi, Natalia; Dundu, A K.T; Willar, Debby (JURNAL ILMIAH MEDIA ENGINEERING, 2017)
Construction activities may be considered successful if they are able to meet the objectives, which are completed at the specified time, in accordance with the cost allocated and meet the implied quality requirements. But in the achievement of the goal is influenced by various factors, one of which is a risk factor. The risks in this case are uncertain circumstances in the construction process that may have adverse impacts or matters that do not correspond to cost, quality or time. The purpose of this study was to identify the risk factors that contractors might experience, determine the level of risk, determine the dominant risk factor and find the risk ratio of the lump sum contract and unit price in terms of cost, time and quality as contractor consideration in decision making determines its contract.The analysis process begins by defining the problem and creating a hierarchical structure consisting of 3 (three) level objectives (level I), criteria (level II) and alternative (level III). This is followed by a pairwise comparison matrix for priority criteria (level II) and alternative (level III) priority weight to obtain the final result of the comparison of lumpsum contract risk and unit cost contract on the construction project from cost, time and quality aspects.The result of analysis with AHP method is obtained that unit price contract more influence to cost aspect which can cause cost swelling than lumpsum contract with ratio 75,79% : 24,21%. The Lumpsum contract has a greater influence over the time aspect that may cause the project completion delay compared to the unit price contract with a ratio of 51,31% : 48,69%. Lumpsum contract has more influence to quality aspect than contract of unit price with ratio 50,86%: 49,14%. Overall use of unit price contracts has a higher priority risk weight than the use of lumpsum contracts with a ratio of 57.87% : 42.13%Based on the results of comparison analysis of lumpsum contract risk and unit price contract, it is expected that the contractor will pay more attention to the dominant risk factors of both contracts before conducting the tender process and signing the contract to anticipate the possibility of risk so that to minimize its impact lead to greater loss.Â Keywords: Risk, Cost, Time, Quality, Lumpsum Contract, Unit Price Contract, Analytic Hierarchy Process (AHP).